Chemical abundances in high-redshift galaxies: a powerful new emission line diagnostic - Dopita, Michael A.; Kewley, Lisa J.; Sutherland, Ralph S.; Nicholls, David C. (Astrophysics and space science, 2016)
This Letter presents a new, remarkably simple diagnostic specifically designed to derive chemical abundances for high redshift galaxies. It uses only the H α , [N ii ] and [S ii ] emission lines, which can usually be observed in a single grating setting, and is almost linear up to an abundance of 12 + log ( O / H ) = 9.05 . It can be used over the full abundance range encountered in high redshift galaxies. By its use of emission lines located close together in wavelength, it is also independent of reddening. Our diagnostic depends critically on the calibration of the N/O ratio. However, by using realistic stellar atmospheres combined with the N/O vs. O/H abundance calibration derived locally from stars and H ii regions, and allowing for the fact that high-redshift H ii regions have both high ionisation parameters and high gas pressures, we find that the observations of high-redshift galaxies can be simply explained by the models without having to invoke arbitrary changes in N/O ratio, or the presence of unusual quantities of Wolf-Rayet stars in these galaxies.